1986
DOI: 10.1152/jappl.1986.60.2.521
|View full text |Cite
|
Sign up to set email alerts
|

Effects of body mass and morphology on thermal responses in water

Abstract: Ten male volunteers were divided into two groups based on body morphology and mass. The large-body mass (LM) group (n = 5) was 16.3 kg heavier and 0.22 cm2 X kg-1 X 10(-2) smaller in surface area-to-mass ratio (AD X wt-1) (P less than 0.05) than the small-body mass (SM) group (n = 5). Both groups were similar in total body fat and skinfold thicknesses (P greater than 0.05). All individuals were immersed for 1 h in stirred water at 26 degrees C during both rest and one intensity of exercise (metabolic rate appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0

Year Published

1994
1994
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(48 citation statements)
references
References 9 publications
1
47
0
Order By: Relevance
“…Like with most cooling techniques, cooling efficiency was affected by body mass; however, brain cooling was not. 4,17 Although larger studies are needed to confirm this finding, it does suggest that the RCD may be a good option for the rapid, noninvasive initiation of brain cooling, even in obese individuals.…”
Section: Discussionmentioning
confidence: 94%
“…Like with most cooling techniques, cooling efficiency was affected by body mass; however, brain cooling was not. 4,17 Although larger studies are needed to confirm this finding, it does suggest that the RCD may be a good option for the rapid, noninvasive initiation of brain cooling, even in obese individuals.…”
Section: Discussionmentioning
confidence: 94%
“…Therefore, it appears that traffic control workers had more effective tissue insulation against heat loss, compared with construction workers 13,14) . In addition, concerning the individual preventive ideas related to clothing against the cold environment being considered to work comfortably in winter, we observed that prevalence of wearing the thermal underwear, body warmer, thermal trousers, underpants, thermal socks, thermal shoes and muffler in the traffic control workers were significantly higher than the construction workers.…”
Section: Subjective Symptoms In the Winter And Prevention Measure Agamentioning
confidence: 97%
“…Skin thermistors (Model 409B, Yellow Springs, OH) were used to measure skin temperature at the following sites: chest, triceps, forearm, thigh, and calf [18]. Rectal, skin and air temperatures were collected by an interface (iNet-100HC, Omega Engineering, Stamford, CT).…”
Section: Measurementsmentioning
confidence: 99%
“…Rectal, skin and air temperatures were collected by an interface (iNet-100HC, Omega Engineering, Stamford, CT). Mean skin temperature (Tsk) was calculated using the formula supported in the current literature [18]: Tsk = (0.22 × calf temperature) + (0.28 × thigh temperature) + (0.28 × chest temperature) + (0.14 × forearm temperature) + (0.08 × triceps temperature).…”
Section: Measurementsmentioning
confidence: 99%